Addressing The Factors Causing Financial Statement Fraud: A Systematic Literature Review And Bibliometric Analysis - Amelia Rachma Archanti; Abdul Rohman (Green Publisher Indonesia, 2024)
Fraud is often revealed through various media and employees are the ones who most often report it. Factors that influence fraud include pressure, opportunity, rationalisation and the ability to commit fraud. This study aims to determine the factors that cause financial statement fraud and find out how to overcome financial statement fraud. This research method uses a systematic literature review of 30 journals that have been selected from scopus, then analysed using VOSviewer_1.6.20 and explained descriptively. Financial statement fraud can be detected using the Beneish model, financial ratios, audit committees, and corporate indicators. The factors that cause it include pressure, opportunity, rationalisation and ability. Based on the data that has been collected, the solution to prevent financial statement fraud is a violation reporting system, honest and ethical corporate culture, good corporate governance, effective internal control and risk management systems, and data analysis and technology. The Beneish model is able to identify manipulator and non manipulator companies. Preventing fraud in banking requires the principle of knowing the customer and anti-money laundering. Anti-fraud strategy should be aligned with organisational strategy with accountability to the board and all employees. Some foreign studies also show ways of prevention such as the intensity of regulatory supervision and auditor sanctions. Future research suggestions are expected that future researchers can conduct research directly in a company and can use this article as additional information in conducting research related to financial statement fraud.